Effectiveness of Maceration Periods with Different Extraction Solvents on in-vitro Antimicrobial Activity from Fruit of Momordica charantia L. - Yang Lin Yeo, Yin Yin Chia, Chin Hong Lee, Heng Sheng Sow, Wai Sum Yap (Journal of Applied Pharmaceutical Science, 2014)
Momordica charantia L. also known as bitter gourd, is one of the medicinal plants that have a long history usage as medicine in Asia for the treatment of various ailments. The present study was aimed to evaluate the effectiveness of maceration periods with various extraction solvents against four gram positive bacteria (B. cereus, B. subtilis, E. faecalis and S. aureus), four gram negative bacteria (E. coli, K. pneumonia, P. aeruginosa and Serratia spp.) and a fungus, C. albicans. Dried fruit powders were extracted at four maceration times (6 h, 12 h, 24 h and 48 h) using different solvents (hexane, petroleum ether, ethyl acetate, acetone, ethanol and distilled water). In the results, gram negative bacteria and fungus were found more susceptible as compared to gram positive bacteria. Solvents with low to intermediate polarity used such as hexane, petroleum ether and ethyl acetate demonstrated better antimicrobial activity as compared to other solvents used. On maceration times used, 6h was found to give the best inhibition zone of the antimicrobial activity with economic feasibility, while on the microorganisms tested, E. coli was found to be the most susceptible, followed by C. albicans and K. pneumonia. Statistical analysis demonstrated significant difference (p < 0.05), where maceration periods, extraction solvents used as well as the type of microorganisms have significant effect on the inhibition zone. Thus, this study revealed the importance of appropriate maceration periods in combination with different extraction solvents used, in giving a satisfactory and reliable result on the antimicrobial activity of the nine potent microorganisms.
Keywords: Antimicrobial activity, Momordica charantia L., Maceration periods, Extraction solvents.